ANALISIS PEMBERIAN REWARD DAN PUNISHMENT PESERTA DIDIK DALAM PENINGKATAN MUTU PENDIDIKAN - Sahade Sahade; Syamsu Rijal (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This study aims to determine: 1) the effect of giving rewards and punishment partially and simultaneously on improving the quality of education and 2) the variables that have a dominant influence on improving the quality of education. The variables in this study are reward as the first independent variable (X1), punishment as the second independent variable (X2) and quality of education as the dependent variable (Y). The population in this study were all students at SMK Negeri 1 Makassar, totaling 1400 students consisting of 415 male students and 985 female students with a total of 40 groups. The sampling technique used purposive sampling technique, the sample was based on interests and limitations so that it takes 5% of the entire population, namely 70 students. The data collection technique used was a questionnaire and relevant school document data. Data analysis techniques used qualitative descriptive analysis with percentages, instrument tests, classical assumption tests and hypothesis testing. Instrument test consists of validity test and reliability test. The classic assumption test consists of a normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The hypothesis test consists of multiple linear regression, simultaneous test (F test), multiple determination coefficient (R2), partial test (t test) and partial determination coefficient ( r2). The results of this study indicate that giving rewards partially has a significant effect on improving the quality of education with a significant level <0.05 and punishment partially has a significant effect on the quality of education with a significant level <0.05. Giving reward and punishment simultaneously has a significant effect on the quality of education with a significant level of <0.05, and the coefficient of determination (R2) is 0.547 (54.7%) which means that the effect of reward and punishment on the quality of education is 54. 7% while the remaining 45.3 is influenced by factors that have not been studied.